Should the varicella‐zoster virus be given to all children to prevent chicken pox?. Issue 9 (September 2017) - O'Dowd, Stacy; Hamood, Heather
Abstract : EVIDENCE‐BASED ANSWER : The administration of the varicella vaccination to healthy, nonimmunized children greatly decreases the incidence of varicella (SOR: B, double‐blind placebo‐controlled efficacy trial). Such vaccination has resulted in an 87% reduction in varicella‐related mortality. The use of the vaccine in immunocompromised children has not been approved by the US Food and Drug Administration.